1991
DOI: 10.3109/10520299109109989
|View full text |Cite
|
Sign up to set email alerts
|

The Standard Romanowsky-Giemsa Stain in Histology

Abstract: A new and technically simple Romanowsky-Giemsa (RG) stain is proposed as a standardized technique for use in histology. An RG stock solution (pure azure B 7.5 g/l, eosin Y as eosinic acid 1.2 g/l in dimethylsulfoxide) is diluted to form the working solution with HEPES-buffer, pH 6. Staining time is 30-90 min after formol-calcium solution (or 2-4 hr after formaldehyde-organic acid mixtures). The resulting overstained sections are to be differentiated. A tannic acid-acetic acid combination in an isopropanol-wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Each question was answered on a scale of 0 to 4, and the total score was calculated. Higher FACE-Q scores in the form of Rasch-transformed responses represent greater objective values for the subjective variables [36]. In case 2, the reconstructed nasal skeleton was examined using CT scanning (Planmeca, Finland) two years after surgery.…”
Section: Assessment Of Resultsmentioning
confidence: 99%
“…Each question was answered on a scale of 0 to 4, and the total score was calculated. Higher FACE-Q scores in the form of Rasch-transformed responses represent greater objective values for the subjective variables [36]. In case 2, the reconstructed nasal skeleton was examined using CT scanning (Planmeca, Finland) two years after surgery.…”
Section: Assessment Of Resultsmentioning
confidence: 99%
“…When Giemsa is used for staining bacteria in tissue section fixed by formaldehyde, the organism stains purple and pink cytoplasm will be seen (Kiernan, 2008). Wittekind et al (1991) found that Giemsa stain seems suitable to replace the Gomori-type trichrome stains under appropriate staining conditions. The staining result depends on many factors such as pH and differentiation and this is in line with current study (Wolf-Dieter, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…In 1892, Dimitri Romanowsky described a technique for staining parasites in blood smear. His method employs the use of methylene blue and its products of oxidation in combination with eosin to stain the blood smear, producing a red nuclei 13, 21 . The method was modified by Wright in 1902 and Giemsa in 1902 and these methods have significantly improved the staining of parasites.…”
Section: Introductionmentioning
confidence: 99%